Raw data for HAWK paper - Marsh, Richard; Cox, Susan; Pfisterer, Karin; Bennett, Pauline; Hirvonen, Liisa; Gautel, Mathias; Jones, Gareth E. (King's College London, 2018)
Raw image sequences for both simulated and experimental data for example shown in Nature Methods HAWK paper. Consists of multi frame image sequences of single molecule fluorescence captured on Richard Marsh's PALM/STORM system with Evolve EMCCD.
Keywords: Localisation Microscopy; Artefacts; High Density; Live Cell